Alcohol-Diluted Deep Eutactic Solvent as the Electrolyte - Rizmahardian Ashari Kurniawan; Hamdil Mukhlishin; Laila Indriani (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
Deep eutectic solvents (DESs) are promising alternatives to traditional electrolytes in electrochemical devices because of their favorable properties, including low volatility, biodegradability, and ease of preparation. This study aimed to optimize a DES composed of choline chloride and urea by investigating the effects of molar ratios and short-chain alcohol additions on viscosity, ionic conductivity, and electrochemical stability. The DES was prepared at 80°C at four molar ratios of choline chloride to urea (1:1, 1:2, 1:3, and 1:4), with a 1:2 ratio optimal for achieving a stable, homogeneous solution. Short-chain alcohols (methanol, ethanol, 1-propanol, and 1-butanol) were added to reduce viscosity and enhance conductivity. The addition of methanol and ethanol effectively lowered the viscosity and increased the ionic conductivity because of their ability to integrate into the DES matrix and disrupt hydrogen bonding. Electrochemical analysis confirmed that the oxidative stability of DESs remained unaffected by these alcohol additions, with oxidation onset consistently at approximately 1 V. These findings demonstrate that methanol and ethanol are suitable additives for improving the performance of DESs as electrolytes in electrochemical applications, enhancing both their conductivity and stability.